DESEMPENHO DE ELETRODOS Pt/C, Pt3Cr/C E PtCr/C PARA APLICAÇÕES EM CÁTODOS DE CÉLULAS A COMBUSTÍVEL DE METANOL DIRETO - Varela Júnior, Jaldyr de Jesus Gomes (2006)
This work presents oxygem reduction reaction (ORR) studies on platinum (Pt/C) and platinum-chromium alloys containing 50% (PtCr/C) or 70% in chromium (Pt3Cr) dispersed on high surface area, in acid aqueous solutions with and without metanol, with cyclic voltammetry, chronoamperometry and rotating disk electrode techniques. Electrochemical measurements have been also performed in a direct methanol unit fuel cell. The electrocatalysts were characterized by energy dispersive X-ray (EDX) and X-ray diffraction (XRD) analyses. The ORR studies in absence of methanol in solution showed that chromium adittion does not change the reaction mechanism observed on the Pt/C and the electrocatalytic activity increases in the order PtCr/C < Pt/C < Pt3Cr/C. Such increase was attributed to a favourable interatomic distance for O2 dissociative adsorption. The alloys showed higher tolerance to methanol presence in solution than Pt, mainly the PtCr electrode due to smaller amount of active sites to methanol adsorption with respect to Pt. In solutions containing low concentration of methanol, the ORR mechanism was not affected by methanol presence. The polarization curves recorded with the unit cell showed that na increase in temperature results in an increase in the electrocatalitic activity of the anode, as well as na increase in methanol diffusion through the Nafion® membrane with consequent cathode depolarization. Furthermore, the system containing Pt3Cr/C as cathodic electrode material presented the best electrochemical performance, with power densities of ~ 55 mW cm-2, in contrast to ~ 40 mW cm-2 for the unit cell with Pt/C cathode and ~ 20 mW cm-2 with PtCr/C.